Penegakan Hukum Terhadap Tindakan Main Hakim Sendiri di Kota Gorontalo - Mobilingo, Mobilingo; Rusmulyadi, Rusmulyadi; Rais, Suardi; Kamuli, Fahmi (Unisan Law Review, 2025)
The purpose of this research: (1) To find out how law enforcement is against vigilantism at the Gorontalo City Police. (2) To determine the obstacles to law enforcement against vigilantism at the Gorontalo City Police. The type of research used in this research is empirical research. is a legal research method that functions to see the law in real terms and examine how the law works in society. The results of this research show that: (1) The policies carried out by the police are divided into two parts, namely policies for victims and policies for perpetrators, for victims the police provide security, handle victims such as taking them to the hospital and conducive to the area where the vigilante action occurred, Meanwhile, for perpetrators, the police carry out investigations in the form of recording or asking for statements from witnesses and then carrying out investigations to collect evidence. (2) The obstacles experienced by the Gorontalo City Resort Police, especially members of the Criminal Investigation Unit, in enforcing the law against criminal acts of taking the law into their own hands in the jurisdiction of the Gorontalo City Police include obstacles from law enforcers and obstacles to public awareness and compliance with the law, in the form of searching for existing evidence. In the field, there is no evidence that shows anyone who participated in taking the law into their own hands because law enforcement against criminal acts of vigilantism in the Gorontalo Police jurisdiction is still not implemented optimally. Keywords: Law Enforcement, Crime, Vigilante